'THE TRUTH IS OUT THERE' - Morris, Meaghan (Cultural Studies, 1997)
This article focuses on aliens. The world is full of people who believe in alien abductions, Satanic conspiracies, and the ineffable evil of government, people who believe that Aborigines are privileged in Australian society, and that minorities have too much power. In short, the body-snatchers are back with, as always, a difference. In 1990s body-snatcher culture, the evil emanates from Western institutions. The truth is out there, but they are right here, insidiously warping reality. They are scientists, doctors, bureaucrats, teachers and academics.